Epidemiology characteristics of chickenpox hospitalizations at Peru Children's Hospital, 2001-2011 - Miranda-Choque, Edwin (2013)
Objective: To determine the epidemiology of chickenpox hospitalizations. Design: Case series study. Setting: National Institute of Child Health, Lima, Peru. Participants: Children with chickenpox. Interventions: Children hospitalized for chickenpox from 2001 to 2011 at Peru’s National Institute of Child Health (INSN) -country without routine vaccination against this infection- were identified from the statistical office data. Main outcome measures: Seasonal variability of children hospitalized with chickenpox. Results: We studied 1 566 children hospitalized for chickenpox, with mean age 2 years 6 months; 46.4% (727/1 466) were female, median hospital stay was 6 days (IQR: 9.4). The most affected group was 0 to 2 years corresponding to 55% (864/1 566). There was seasonal distribution in months’ frequency with annual increasing trend. Cases of chickenpox with some complication were 68.5% (1 073/1 566), and 0.83% (13/1 493) died. Conclusions: Hospitalizations for chickenpox in the INSN is a major cause of morbidity, with seasonal trend, more frequent from November to February, with tendency to annual increase; it represents a significant economic burden.